Pengembangan E-Modul Asam Basa Berbasis Problem Based Learning melalui Google Classroom pada Sekolah Menengah Kejuruan (SMK) - Abdullah, Asriyani; Danial, Muhammad; Anwar, Muhammad (Program Pasca Sarjana UNM, 2021)
This research is a development research that aims to develop and produce an acid- base e-module based on problem-based learning through google classroom at a vocational high school (SMK) which has valid, practical, and effective criteria. The development model used in the study refers to the 4D development model, which consists of the definition stage, the design stage, the development stage, and the dissemination stage. The acid-base e-module based on problem-based learning developed was validated by two experts. After being validated, the acid-base e-module based on problem-based learning was piloted on students at grade X TKJ 1 at SMKN 5 Jeneponto of academic year 2020/2021 with 27 students. The results show that the acid-base e-module based on problem-based learning developed had conducted a validation process, measuring the level of practicality and effectiveness. The e-module is stated as valid based on the results of the e- module validation with an average value of 3.27 (valid). The e-module is stated as practical based on: (1) the implementation of the acid-base e-module based on problem-based learning at an average value of 1.9 (fully implemented), (2) the teacher's response with an average score of 97.12 (very practical), and (3) the students’ responses with an average score of 81.34 (very practical). E-module is stated as effective based on the results of the N-gain test of 0.76 (high) and classical completeness of 85.19%. Therefore, the results of the study indicate that the acid-base e-module based on problem-based learning has valid, practical, and effective qualities. An outline summary of the acid-base e-module based on problem-based learning through Google Classroom contains a glossary, basic competencies, competency achievement indicators, instructions for using e- modules, concept maps, learning activities 1, 2, and 3, evaluation and answer keys.